2004
DOI: 10.1097/01.pec.0000113880.10140.19
|View full text |Cite
|
Sign up to set email alerts
|

Acute Presentation of Infected Urachal Cysts

Abstract: Urachal remnants, although relatively rare, masquerade as a large number of diverse disorders leading to a high rate of misdiagnosis. A typical case is reported in which a 10-year-old boy presented to the Emergency Department twice before being incorrectly diagnosed with a pelvic or lower abdominal periappendiceal abscess. Definitive diagnosis and treatment of an infected urachal cyst were made intraoperatively. A review and discussion of urachal remnants is presented, and a diagnostic algorithm and treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Urachal cysts usually become symptomatic when these are infected. Infected urachal cysts present with fever, abdominal pain, abdominal tenderness with erythema, lower abdominal mass, nausea, vomiting, and dysuria [ 4 ]. The diagnosis of urachal cysts is mainly clinic and the diagnosis is usually confirmed by ultrasonography, computed tomography (CT), and also magnetic resonance imaging (MRI).…”
Section: Discussionmentioning
confidence: 99%
“…Urachal cysts usually become symptomatic when these are infected. Infected urachal cysts present with fever, abdominal pain, abdominal tenderness with erythema, lower abdominal mass, nausea, vomiting, and dysuria [ 4 ]. The diagnosis of urachal cysts is mainly clinic and the diagnosis is usually confirmed by ultrasonography, computed tomography (CT), and also magnetic resonance imaging (MRI).…”
Section: Discussionmentioning
confidence: 99%
“…Resulting complications include secondary infection, peritoneal rupture, cancer, fistula, acute hemorrhage, urinary or intestinal obstruction, and Reiter syndrome 1,8…”
Section: Discussionmentioning
confidence: 99%
“…This complicated urachal anomaly requires a surgical excision to prevent symptomatic recurrence and malignant degeneration. 1 However, traditional open excisions are associated with significant morbidity and prolonged convalescence 2…”
Section: Introductionmentioning
confidence: 99%
“…Allen et al5 and Ozbek et al11 suggested that ultrasonography is an ideal modality for diagnosing urachal cysts, since these entities are cystic, extraperitoneal, and are directly related to the bladder. Nagasaki et al17 reported a 75% diagnostic success rate for ultrasound, whereas Minevich et al4 reported 57.1% and Cilento et al18 reported 100%.…”
Section: Discussionmentioning
confidence: 99%